The framing of antimicrobial use and resistance by Irish agricultural newspapers during a period of key European Union policy changes - Luke-Currier, Addiena Marie; Hodkinson, Trevor; Moriarty, Elaine (Springer Nature, 2026)
Antimicrobial resistance (AMR) is a societal problem which is often linked to agricultural use of antimicrobials in addition to human medicine. This has resulted in the development of policies at the European Union and Member State level to regulate farmers’ antimicrobial use (AMU) practices. Our aim is to understand how AMU, AMR, and related policies are framed within agricultural newspapers in Ireland and how this may have changed over time. A total of 2,019 articles from 2014 to 2024 were analyzed using Matthes and Kohring’s (2008) mixed methods approach. Four frames emerged: 1) Agricultural Community Action Against AMR, 2) Imposition of Legal Action on Antimicrobials, 3) AMU on the Farm, and 4) Addressing the AMR Threat Together. Frames vary in their inclusion of the issue of AMR, related policies, and actors across different levels of the agricultural sector. The different frames reflect the conflicting values, including One Health concerns for animal, human, and/or environmental health as well as economic interests, that drive proposed solutions to AMR. Frame 2 gained prominence from 2020 to 2022 after key EU regulations on AMU were signed. Following these changes, the way the issue was framed shifted and the relationships of farmers to other agricultural actors and their significance within the wider rural community came to the fore of the discussion. These results highlight the impacts that policy changes to farming practices can have on the wider society and the social factors which underly them.
PUBLISHED
Keywords: Antimicrobial resistance; Agricultural regulations; Farming practices; Framing; One health; Rural communities; ANTIMICROBIAL RESISTANCE; Agricultural Planning/Policy; NEWSPAPER COVERAGE